Effectiveness of peri-abortion counselling in preventing subsequent unplanned pregnancy: a systematic review of randomised controlled trials. Issue 1 (7th September 2015) - Stewart, Hannah; McCall, Stephen J; McPherson, Calum; Towers, Lucinda C; Lloyd, Bethany; Fletcher, Jack; Bhattacharya, Sohinee
Abstract : Objective: This systematic review and meta-analysis assessed whether enhanced peri-abortion contraceptive counselling had an effect on subsequent unplanned pregnancies and the uptake and continuation of contraceptive methods. Methods and materials: A systematic review of English-language articles published prior to May 2014 was conducted, using MEDLINE, EMBASE and the Cochrane Library. Only randomised controlled trials (RCTs) involving enhanced pre- and post-abortion contraceptive counselling were included. The authors independently applied the inclusion and exclusion criteria to the identified records, and extracted data from each included paper using a predefined extraction form. Risk of bias was assessed using the Cochrane Collaboration's tool. Meta-analyses were undertaken where appropriate and based on random effects models. Results: Six RCTs met the inclusion criteria. Three RCTs investigated the effect of enhanced counselling on subsequent unplanned pregnancy. The results of the meta-analysis were non-significant [pooled odds ratio (OR) 0.47; 95% confidence interval (95% CI) 0.12–1.90]. Four RCTs reported results relating to the uptake of long-acting reversible contraception (LARC) and continuation of chosen method of contraception at 3 months. Findings were non-significant (pooled OR 1.07; 95% CI 0.20–5.69 and pooled OR 3.22; 95% CI 0.85–12.22, respectively). Conclusions: This review found no evidence of effect resulting from enhanced peri-abortion contraceptive counselling on subsequent unplanned pregnancy rate or the uptake of LARC. However, these findings are limited by the small number of relevant studies available and the marked heterogeneity between published studies. Further, larger-scale RCTs should be undertaken to ensure that there is sufficient power to detect an effect.